Ligands modification strategies for mononuclear water splitting catalysts - Wang, Lei; Wang, Lijuan (Frontiers in Chemistry, 2022)
Artificial photosynthesis (AP) has been proved to be a promising way of alleviating global climate change and energy crisis. Among various materials for AP, molecular complexes play an important role due to their favorable efficiency, stability, and activity. As a result of its importance, the topic has been extensively reviewed, however, most of them paid attention to the designs and preparations of complexes and their water splitting mechanisms. In fact, ligands design and preparation also play an important role in metal complexes’ properties and catalysis performance. In this review, we focus on the ligands that are suitable for designing mononuclear catalysts for water splitting, providing a coherent discussion at the strategic level because of the availability of various activity studies for the selected complexes. Two main designing strategies for ligands in molecular catalysts, substituents modification and backbone construction, are discussed in detail in terms of their potentials for water splitting catalysts.